Seismic ridge subduction and topography: Foreland deformation in the Patagonian Andes - Ramos, Victor Alberto (Tectonophysics)
The Patagonian Andes recorded several episodes of active ridge subduction in the last 80 million years. An analysis of the spatial and temporal relation between the present segment of collision of the Chile ridge and the digital topography of the foreland shows a correlation with the beginning of deformation and uplift in the inner sector of the Patagonia fold and thrust belt. Several magmatic episodes related to the collision such as near trench magmatism, adakite emplacement, OIB plateau basalts in the retroarc, and the arc volcanic gap, are associated with the uplift and deformation of the Patagonian Cordillera. Based on these correlations, a collision of the Aluk (or Phoenix)-Farallon ridge during Paleogene times south of 43°30′ is identified. Changes in magmatic patterns, molasses deposits, deformation and uplift of the Patagonian Cordillera constrain the region affected by the collision. Similar evidence implies a third period of collision in the Late Cretaceous, based on the occurrence of adakitic rocks, arc magmatic gap, and deformation along the southern Patagonian Andes. This earliest hypothesized collision would require the existence of a new oceanic microplate between the Pacific and the Aluk plates during Late Cretaceous times. Present rapid isostatic rebound related to the continental ice cap retreat in the Patagonian Andes is restricted to the region south of Chile triple junction (46°30′S). The uplift rate here is more than two times more rapid than normal isostatic rebounds recorded in the Northern Hemisphere, and requires an abnormally hot mantle with low viscosity. This abnormal mantle may be a consequence of several episodes of ridge collision and development of asthenospheric windows that are inconsistent with periods of cold flat-slab subduction proposed by some authors to explain the arc volcanic gaps. Fil: Ramos, Victor Alberto. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Instituto de Estudios Andinos "Don ...